2023
DOI: 10.3389/fpls.2023.1211104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airflow angle on abaxial surface deposition in air-assisted spraying

Abstract: Air-assisted sprayers are widely used in orchards for pest and disease control. However, air-assisted spray deposition on the abaxial surface of leaves is often limited. In this study, a method to achieve satisfactory spray deposition on the abaxial leaf surface and an assessment of factors that affect abaxial surface deposition were investigated. The effects of leaf angle, wind speed, platform velocity, and nozzle type were assessed. Abaxial surface coverage was significantly affected by leaf angle, wind spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…43 Whether it is the vortex airflow from unmanned aerial vehicle or the parallel airflow from an air-assisted boom-sprayer, wind loads are applied to the branches and leaves of the crop canopy by higher wind speeds, forcing flexible branches and leaves to bend and deform, increasing porosity and opening the transport channel for droplets to enter the interior of the crop canopy. [43][44][45] The droplets can be forced to change their trajectory inside the branch and leaf apertures by the airflow. [46][47][48][49] However, research has shown that using vortex airflow can cause more blade displacement and branch disturbance compared to parallel airflow.…”
Section: Discussionmentioning
confidence: 99%
“…43 Whether it is the vortex airflow from unmanned aerial vehicle or the parallel airflow from an air-assisted boom-sprayer, wind loads are applied to the branches and leaves of the crop canopy by higher wind speeds, forcing flexible branches and leaves to bend and deform, increasing porosity and opening the transport channel for droplets to enter the interior of the crop canopy. [43][44][45] The droplets can be forced to change their trajectory inside the branch and leaf apertures by the airflow. [46][47][48][49] However, research has shown that using vortex airflow can cause more blade displacement and branch disturbance compared to parallel airflow.…”
Section: Discussionmentioning
confidence: 99%